Structural and optical characterization of ZnS nanoparticles - Sharma, *Ravi (International Multidisciplinary Research Journal, 2011)
The present paper reports the structural and optical characterization of the ZnS nanoparticles, where as mercaptoethanol (ME) was used as the capping agent. Nanoparticles of zinc sulphide were prepared by chemical route technique. The particle size of such nanocrystals was measured using XRD pattern and it is found to be in between 3nm - 5nm. The blue-shift in the absorption spectra was found with reducing size of the nanoparticles. It was also found that the change in Mn concentrations does not influence the particle size and blue-shift in the absorption spectra. The optical absorption edge was found at 280 nm for all the doped samples for fixed concentration of capping agent. The particle size of nanoparticle has been calculated both theoretically and experimentally, which is nearly the same. The FTIR spectra inferred that the stabilizing agent passivates the surface of the particles.